2015
DOI: 10.3171/2015.3.peds14417
|View full text |Cite
|
Sign up to set email alerts
|

SMARCE1 mutations in pediatric clear cell meningioma: case report

Abstract: Clear cell meningioma (CCM) is an uncommon variant of meningioma. The authors describe a case of a pediatric CCM localized to the lumbar spine. After resection, sequencing revealed an inactivating mutation in the SWI/SNF chromatin remodeling complex subunit SMARCE1, with loss of the second allele in the tumor. The authors present a literature review of this mutation that is associated with CCM and a family history of spine tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…Furthermore, germline SMARCE 1 (SWItch/sucrose non-fermentable-related matrixassociated actin-dependent regulator of chromatin subfamily E member 1) mutations have been linked with spinal and cranial clear cell meningiomas. 15,16 Smith et al identified SMARCE 1 mutations and loss of SMARCE 1 proteins in patients and paraffinembedded tissue blocks of spinal and cranial clear cell meningioma cases. 15 The treatment of choice for clear cell meningiomas is total surgical resection, with radiotherapy and chemotherapy being reserved for recurrent cases.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, germline SMARCE 1 (SWItch/sucrose non-fermentable-related matrixassociated actin-dependent regulator of chromatin subfamily E member 1) mutations have been linked with spinal and cranial clear cell meningiomas. 15,16 Smith et al identified SMARCE 1 mutations and loss of SMARCE 1 proteins in patients and paraffinembedded tissue blocks of spinal and cranial clear cell meningioma cases. 15 The treatment of choice for clear cell meningiomas is total surgical resection, with radiotherapy and chemotherapy being reserved for recurrent cases.…”
Section: Resultsmentioning
confidence: 99%
“…The most common are germline NF2 mutations, responsible for neurofibromatosis type 2 (NF2) . Two genes ( SMARCB1 and SMARCE1 ), encoding two proteins of the SWI/SNF complex (BAF47 and SMARCE1), have also been recently implicated in hereditary meningiomatosis (, cf. review in ).…”
Section: Introductionmentioning
confidence: 99%
“…In case of CCM, germline loss‐of‐function mutations in the SMARCE1 chromatin remodelling factor were identified as a cause of both spinal and cranial CCM . To date, 12 families with SMARCE1 ‐associated CCM have been reported (Table ) . SMARCE1 mutations appear to be specific for the clear cell histological subtype, rather than tumour location or syndromic presentation .…”
Section: Introductionmentioning
confidence: 99%
“…8,14 To date, 12 families with SMARCE1-associated CCM have been reported (Table 1). 14-18 SMARCE1 17 †Discussed in more detail in Raffalli-Ebezant et al 2015. 15 mutations appear to be specific for the clear cell histological subtype, rather than tumour location or syndromic presentation.…”
Section: Introductionmentioning
confidence: 99%